Kenaf/Glass Hybrid Composites: Preparation, Characterization And Properties - Abdul Malek Ya’acob, Abdul Malek (2013)

(untitled)
This research involved the use of long kenaf fiber and glass fiber fabric grade commercial aircraft and its potential to be used in composite production. Hybrid kenaf/glass fiber epoxy composites have been fabricated using untreated and treated kenaf. Kenaf treatment was done using sodium hydroxide and acetylation process to modify the surface of the kenaf fibers. In this study no modification was done on the surface of glass fibers or the matrix. This study combines glass fiber commonly used on aircraft with kenaf fiber using interply hybrids concept. The fabrication method that has been used to combine the kenaf and glass fiber to produce composite is hand lay-up and vacuum bagging method. Hybrid samples of kenaf and glass fiber produced for this study utilized the bidirectional orientation concept where one fiber layers is align in the ‘weft’ direction and the second fiber layers is align in the ‘warp’ direction. Characterization and study of the properties of hybrid kenaf/glass fiber composites was determined by morphological of adhesion, physical, thermal and mechanical. Inconsistent mechanical properties behavior for untreated kenaf /glass fiber composites samples was confirmed by the high void content between fiber and matrix that can reach up to 300% with comparison to treated samples. Kenaf fiber treated/glass composites showed a consistency in bending characteristics and impact strength at low percentage by weight of kenaf fiber namely at 10 wt%, 20 wt% and 30 wt% kenaf.